Design and Rationale of the GAUSS‐2 Study Trial: A Double‐Blind, Ezetimibe‐Controlled Phase 3 Study of the Efficacy and Tolerability of Evolocumab (AMG 145) in Subjects With Hypercholesterolemia Who Are Intolerant of Statin Therapy. Issue 3 (29th January 2014) - Cho, Leslie; Rocco, Michael; Colquhoun, David; Sullivan, David; Rosenson, Robert S.; Dent, Ricardo; Xue, Allen; Scott, Rob; Wasserman, Scott M; Stroes, Erik
Abstract Statins effectively lower low‐density lipoprotein cholesterol (LDL‐C), reducing cardiovascular morbidity and mortality. Most patients tolerate statins well, but approximately 10% to 20% experience side effects (primarily muscle‐related) contributing to diminished compliance or discontinuation of statin therapy and subsequent increase in cardiovascular risk. Statin‐intolerant patients require more effective therapies for lowering LDL‐C. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a compelling target for LDL‐C–lowering therapy. Evolocumab (AMG 145) is a fully human monoclonal antibody that binds PCSK9, inhibiting its interaction with the LDL receptor to preserve LDL‐receptor recycling and reduce LDL‐C. Phase 2 studies have demonstrated the safety, tolerability, and preliminary efficacy of subcutaneous evolocumab in diverse populations, including statin‐intolerant patients. This article describes the rationale and design of the Goal Achievement After Utilizing an anti‐PCSK9 Antibody in Statin‐Intolerant Subjects 2 (GAUSS‐2) trial, a randomized, double‐blind, ezetimibe‐controlled, multicenter phase 3 study to evaluate the effects of 12 weeks of evolocumab 140 mg every 2 weeks or 420 mg every month in statin‐intolerant patients with hypercholesterolemia. Eligible subjects were unable to tolerate effective doses of ≥2 statins because of myalgia, myopathy, myositis, or rhabdomyolysis that resolved with statin discontinuation. The primary objective of the study is to assess the effects of evolocumab on percentage change from baseline in LDL‐C. Secondary objectives include evaluation of safety and tolerability, comparison of the effects of evolocumab vs ezetimibe on absolute change from baseline in LDL‐C, and percentage changes from baseline in other lipids. Recruitment of approximately 300 subjects was completed in August 2013.